Incidence and Risk Factors of the COVID-19 Pandemic: An Epidemiological Approach - Alberto Arnedo-Pena; Francisco Guillen-Grima (MDPI AG, 2023)
After three years of the COVID-19 pandemic, it is certain that the SARS-CoV-2 virus has been a turning point for humanity in both developed and developing countries [...]